'Some glimpses of an Asian PhD journey in tourism' – An ethnodrama. (October 2021) - Mura, Paolo; Wijesinghe, Sarah N.R.; Matar, Motaz H.
Abstract: By combining three different genres – academic writing, theatrical playwriting and performing – this article presents different ways of knowing and representing realities for tourism scholars. More specifically, drawing upon social scientists' influential work on performance texts and an ethnodramatic script written by the authors based on dramatized ethnographic and autoethnographic fieldwork, it portrays a tourism PhD journey in an Asian institution. As an attempt of representing the power structures underpinning academia (and tourism academia), namely postcolonial, gendered, global, regional, institutional, and socio-cultural forces, among others, the 8 scenes constituting the script (one of which is enacted and presented in a video) discuss how Asian PhD journeys are shaped by specific approaches to supervision, issues of authorship, gendered dynamics and postcolonial legacies. The main rationale behind this work lies in the recognition of the powerful/performative role of embodied texts and performances in producing, shaping and re-presenting realities. More specifically, the ethnodrama presented in this paper and its embodied representation act as vehicles that are both political and entertaining in producing meanings. Highlights: It presents three genres: academic writing, theatrical playwriting and performing. It portrays a tourism PhD journey in an Asian institution. It discusses the power structures underpinning tourism academia. It discusses PhD supervision, authorship, gender and postcolonialism in academia.